Antimicrobial and antioxidant potential of Lavandula pedunculata extracts and their inhibitory action against Candida albicans - HANANE BAKRIM; MERIEM MABCHOUR; OUIAM EL GALIOU; ABDELHAY ARAKRAK; MOHAMMED BAKKALI; AMIN LAGLAOUI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bakrim H, Mabchour M, El Galiou O, Arakrak A, Bakkali M, Laglaoui A. 2024. Antimicrobial and antioxidant potential of Lavandula pedunculata extracts and their inhibitory action against Candida albicans. Biodiversitas 25: 4020-4032. Lavandula pedunculata (Mill.) Cav. is an aromatic and medicinal plant that has attracted widespread interest due to its numerous potential applications in the food and pharmaceutical industries. Our study aimed to investigate the biological activities of organic extracts obtained from L. pedunculata using Soxhlet extraction by n-hexane, dichloromethane, methanol, and distilled water. Extracts were evaluated for their antibacterial, antifungal, and antioxidant potential. Although these extracts did not display any antibacterial effect, we observed a significant effect against Candida albicans. The aqueous L. pedunculata extract exerted a bacteriostatic effect (11±1 mm, MIC=>40 mg/mL) and inhibited the formation of C. albicans biofilms (78.8%). Moreover, the aqueous fraction had the greatest potential to curb exopolysaccharide production and protein release, with OD values lower than control. Antifungal screening revealed that methanolic and dichloromethane extracts of L. pedunculata exerted the highest activity against Botrytis cinerea and Fusarium oxysporum as both extracts exert a fungistatic action (100% inhibition at 10 mg/mL). Antioxidant potential was particularly strong in the methanolic extract, as revealed by DPPH and FRAP assays (IC50= 0.012 mg/mL). Phytochemical screening showed a strong correlation between phenolic content and antioxidant effect. LC-MS analysis of the aqueous fraction detected the presence of glucuronide and glucoside conjugates of quercetin and kaempferol, apigenin, and vanillic acid, which are indicative of rich polyphenolic content.